2021
DOI: 10.14254/2071-789x.2021/14-2/5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public governance on the economic growth: Evidence from gulf cooperation council countries

Abstract: This study aims to examine how public governance impacts and affects economic growth in the Gulf Cooperation Council (GCC) which was established on 25th May 1981 and is active till to date, and whether public governance indicators significantly influence the economic growth of these countries. The study's sample includes the six GCC countries in the period of 1996-2019. The study model tests the effects of the independent variables of public governance which are the worldwide governance indicators on the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…The positive coefficient suggests that a one percent increase in government effectiveness enhances Tanzania's economic growth by 1.485 percent assuming all other parameters remain constant. The findings support the underlying hypothesis of the study as well as other studies that have indicated that government effectiveness is positively associated to development (Al-Naser, 2021;Nsiah & Fayissa, 2013;Adzima, 2019;Afolabi, 2019;Azimi, 2020).…”
Section: Table 2 Impact Of Governance On Economic Growthsupporting
confidence: 90%
See 1 more Smart Citation
“…The positive coefficient suggests that a one percent increase in government effectiveness enhances Tanzania's economic growth by 1.485 percent assuming all other parameters remain constant. The findings support the underlying hypothesis of the study as well as other studies that have indicated that government effectiveness is positively associated to development (Al-Naser, 2021;Nsiah & Fayissa, 2013;Adzima, 2019;Afolabi, 2019;Azimi, 2020).…”
Section: Table 2 Impact Of Governance On Economic Growthsupporting
confidence: 90%
“…The findings support the study's prior hypothesis as well as other research that showed political stability, voice and accountability, rule of law, and government effectiveness to be positively associated with development (Teke, 2012;Afolabi, 2019;Adenuga, 2013). Therefore, government efficacy has a favorable and considerable impact on Tanzania's economic growth (at a 5% level) (Al-Naser, 2021;Nsiah & Fayissa, 2013;Adzima, 2019;Afolabi, 2019;Azimi, 2020). The positive coefficient suggests that a one percent increase in government effectiveness enhances Tanzania's economic growth by 1.485 percent assuming all other parameters remain constant.…”
Section: Table 2 Impact Of Governance On Economic Growthsupporting
confidence: 87%
“…Evidence of the substantial impact of the shadow economy on human development, including its economic dimension valued by GDP, is available in the research of Mishchuk et al (2018), Navickas et al (2020). Some partial factors of social injustice, like corruption, violation of the role of the law, or obstacles to doing business are investigated in empirical studies fulfilled by Al-Naser & Hamdan (2021), Leal Rodríguez & Sanchís Pedregosa (2019. Arrording to (Wang et al, 2021) lack of social supports or even lower level of social support has a negative impact on the quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Significant negative changes have taken place in the world economy (Tommaso, 2020), consumption (Minchenko & Demchuk, 2021), insurance (Hinrichs & Bundtzen, 2021), the green bond market (Keliuotytė-Staniulėnienė & Daunaravičiūtė, 2021), and business in general (Antonyuk, 2021;Tiutiunyk et al, 2021), healthcare (Androniceanu, 2020), the banking sector (Bernardelli et al, 2021), etc. That is why there is a need for a systematic restructuring of approaches to ensure the countries' readiness to combat and prevent mass diseases (Al-Naser & Hamdan, 2021;Dutta et al, 2020;Bilan et al, 2019). In this context, the study by researchers of determinants of the impact on the country's health profile formation is a priority.…”
Section: Literature Reviewmentioning
confidence: 99%